2019
DOI: 10.1038/s41598-019-53465-y
|View full text |Cite
|
Sign up to set email alerts
|

Andean Tectonics and Mantle Dynamics as a Pervasive Influence on Amazonian Ecosystem

Abstract: The Amazonian landscape evolution is the result of the combined effect of Andean tectonism, climate and the Earth’s interior dynamics. To reconstruct the landscape evolution and its influence on paleoenvironmental variations within Amazonia since the Oligocene, we conducted numerical experiments that incorporate different surface and geodynamic processes, reproducing many paleogeographic features as inferred from the sedimentary record. We show that the evolution of the drainage pattern gradually reduced the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
89
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(107 citation statements)
references
References 50 publications
(75 reference statements)
4
89
1
Order By: Relevance
“…This fluvial landscape is thought to have initiated in western Amazonia from c. 9 Ma and enabled colonization by a mix of grass-dominated and forest vegetation (Latrubesse et al 2010). Similarly, the numerical models of Bicudo et al (2019) propose a transition towards a mosaic of forest, floodplain grasslands and lakes. On account of this massive change in the geographic landscape, our second hypothesis (H2) suggests that during this period, extensive mountain uplift and megafan formation triggered high-energy fluvial environments (9 to 3.5 Ma), opening up large open spaces in the Andean foothills and slopes where grasses were important pioneer species.…”
Section: Landscape Dynamics Set the Scene For Grass Expansionmentioning
confidence: 98%
See 1 more Smart Citation
“…This fluvial landscape is thought to have initiated in western Amazonia from c. 9 Ma and enabled colonization by a mix of grass-dominated and forest vegetation (Latrubesse et al 2010). Similarly, the numerical models of Bicudo et al (2019) propose a transition towards a mosaic of forest, floodplain grasslands and lakes. On account of this massive change in the geographic landscape, our second hypothesis (H2) suggests that during this period, extensive mountain uplift and megafan formation triggered high-energy fluvial environments (9 to 3.5 Ma), opening up large open spaces in the Andean foothills and slopes where grasses were important pioneer species.…”
Section: Landscape Dynamics Set the Scene For Grass Expansionmentioning
confidence: 98%
“…Perennial grasses such as described by Junk (1997a) would have formed part of the plant community. Recent numerical models by Bicudo et al (2019) provide a further basis for this scenario and explain the sedimentary basin development that accommodated such a wetland. These authors suggest that várzea gradually extended from the eastern Andean slopes into Amazonia, as the wetland development progressed.…”
Section: Landscape Dynamics Set the Scene For Grass Expansionmentioning
confidence: 99%
“…Some studies suggest that forests growing on ADEs can be compositionally and structurally distinct from surrounding vegetation (Clement et al., 2009; Junqueira, Shepard, & Clement, 2010; Palace et al., 2017) and may contribute to the diverse and heterogeneous tree flora of Amazonia (Aragão et al., 2009; Sombroek, 1966). To date, understanding the mechanisms that determine the composition, structure and diversity of Amazonia forests is a major challenge (Bicudo, Sacek, Almeida, Bates, & Ribas, 2019; Hoorn et al., 2010; Levis et al, 2017). While studies have suggested the importance of past land‐use as a factor in increasing the diversity and distribution of current species (Cook‐Patton et al., 2014; Levis et al, 2017), it is unclear whether edaphic factors associated with ADE soils also influence species richness in Amazonia.…”
Section: Introductionmentioning
confidence: 99%
“…Ribas et al 2019) change. Although the conceptual models for longer time scales have been quantitatively evaluated in continental-scale numerical models (Sacek, 2014, Bicudo et al, 2019, the short-term effects of climate and eustasy require a novel approach that considers the particularities of that specific time and geographical scales.…”
Section: Introductionmentioning
confidence: 99%
“…One of the processes that the known large-scale and long-term models (e.g. Sacek, 2014, Bicudo et al, 2019 do not reproduce is the lateral erosion of valley margins and older terraces resulting from lateral migration of channels. This pro cess is essential to the formation and widening of the in-valley floodplains, which is an important element in the central Amazonia because it is in the floodplains that Várzea an d Igapó biomes develop.…”
Section: Introductionmentioning
confidence: 99%